Den neoklassiske frihandelsfejlslutning - Kure, Nikolaj (K&K - Kultur og Klasse, 2017)
Free trade has traditionally been seen as an indisputable ‘moral law’ that benefits all trading partners and thus stimulates peaceful relations between nations. However, recent years have seen the emergence of a whole range of critical voices that articulate various types of free trade critique. The overall intention of the current paper is to discuss this tendency by reviewing Hermann Daly’s critique of the free trade argument as found in neoclassical economic theory. Daly’s argument is that neoclassical theorists on the one hand posit David Ricardo’s theory of comparative advantage as the overarching argument for free trade while on the other hand pushing through free trade arrangements in which Ricardo’s theory ceases to work. In more concrete terms: Ricardo’s theory shows that all trade partners benefit from free trade as long as capital cannot be allocated across national borders, yet current free trade agreements are representative of a neoliberal ideology that opposes all kinds of trading barriers, including national borders. On this basis, it seems reasonable to conclude that proponents of free trade use Ricardo’s argument as a strawman to build a neoliberal world economy based on absolute advantages.